A Systematic Review and Bibliometric Analysis of Studies on Generation Z and the Hotel Industry: Past, Present and Future Agenda - Toboso-Gómez, José Damián; Mercade-Mele, Pere; Almeida-García, Fernando; Siyamiyan-Gorji, Abolfazl (MDPI, 2025)
Generation Z is becoming a dominant market segment and an essential source of talent in the hospitality industry. Their digital fluency, sustainability expectations, and preference for meaningful and personalized experiences are increasingly reshaping service delivery, marketing strategies, and workforce management in the hotel industry. Following the PRISMA 2020 guideline, this review systematically analyzed 131 peer-reviewed studies published between 2011 and 2025. Performance analysis, science mapping through coword and Leiden clustering, and trend analysis were conducted using VOSviewer (v1.6.20) and Biblioshiny in RStudio (v2025.09.2). The findings reveal a rapidly expanding but relatively young field, with key themes clustered around technology acceptance (AI, service robots), experiential and sustainable consumption, digital engagement (word-of-mouth, social media), workforce dynamics (person–environment fit, leadership, quiet quitting), and emerging topics such as experiential education, ethics, and self-efficacy. The study highlights the centrality of the Theory of Planned Behavior and technology acceptance models in explaining Gen Z’s decision-making, while also identifying substantial gaps in cross-cultural, ethical, and experiential research. Practical implications call hoteliers to integrate seamless digital services, robust sustainability initiatives, and adaptive talent management system to meet Gen Z’s evolving expectations.
Keywords: Hostelería - Marketing; Generación Z - Aspectos sociales; Generation Z; Hotel industry; Systematic analisis; Accommodation